Maintenance of immunization indicators in times of a pandemic: reflections of nursing students (Research, Society and Development, 2022)
The objective of this article is to describe the experience of nursing students in the operationalization of an immunization campaign proposed by the Health Department of a municipality in the interior of the northern region of the state of Ceará, together with Primary Health Care (PHC). Descriptive study with a qualitative approach of the experience report type that took place during the period from September to November 2020 in an immunization campaign focused on monitoring and replacing the vaccination status of children in the municipality. The experience took place with the participation of 58 nursing students working within 26 Family Health Centers (CSF) through monitoring, interviewing and vaccination of the target audience, children aged between 2 months and 4 years and 11 months. and 29 days that were registered at the CSF where the work was carried out and were part of the mapped territory. With the experience of the academics, it was clear that the COVID-19 pandemic affected the vaccination situation of children in the municipality through social isolation, but other aspects that interfere in the updating of vaccines are also worth mentioning, such as digital inclusion. of health professionals, use of immunization data feed systems, fake news about vaccines, among others.